A method for preparing high dielectric constant lead zirconate titanate film

By adding transition metal oxides and polyvinyl alcohol aqueous solution in the preparation process of lead zirconium titanate film, and using magnetron sputtering and rapid heat treatment technology, the problem of poor dielectric constant in the high frequency range of lead zirconium titanate film is solved, and the effect of maintaining high dielectric constant and low dielectric loss in a wide frequency range is achieved.

CN116145094BActive Publication Date: 2025-03-25QUANZHOU NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310024541.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2025-03-25
Estimated Expiration
2043-01-09

AI Technical Summary

Technical Problem

The dielectric constant of the existing lead zirconium titanate film rapidly decreases near the resonant frequency, and the high dielectric constant value is mainly concentrated in the low frequency range. The dielectric constant in the high frequency range is poor, which affects its actual production and application.

Method used

A high-dielectric constant lead zirconium titanate film is used, which includes mixing PbO, TiO2 and ZrO2 at a certain mass ratio, and adding polyvinyl alcohol aqueous solution for grinding and sintering, then adding transition metal oxide for secondary sintering, and finally forming a high-dielectric constant lead zirconium titanate film through magnetron sputtering and rapid heat treatment.

Benefits of technology

It realizes maintaining a high dielectric constant over a wide frequency range, improves the dielectric performance of lead zirconium titanate film, is suitable for the preparation of high-frequency devices, and reduces the annealing temperature of the film, and increases the energy storage density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116145094B_ABST
    Figure CN116145094B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high dielectric constant lead zirconate titanate film, comprising the following steps: 1) mixing PbO, TiO2 and ZrO2 in a certain mass ratio, adding a polyvinyl alcohol (PVA) aqueous solution after mixing, grinding fully, pressing into a target, and then sintering once; 2) ball-milling the material sintered in step 1), adding a transition metal oxide thereto, grinding fully, pressing into a target, and then sintering twice to obtain a doped lead zirconate titanate target material after sintering; 3) depositing a lead zirconate titanate film on the doped lead zirconate titanate target material obtained after sintering by a magnetron sputtering method, and sputtering at a certain power density; 4) subjecting the lead zirconate titanate film to rapid heat treatment to obtain a high dielectric constant lead zirconate titanate film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high dielectric constant lead zirconate titanate film. Background Art

[0002] Energy storage capacitors have broad applications in pulse power supplies, new energy vehicle inverters, embedded capacitors, etc. Dielectric materials with high energy storage density can meet the demand for capacitor materials. Since lead zirconate titanate (PZT) ferroelectric thin film is an ABO3 type perovskite phase compound, when the chemical composition is near the quasi-isotropic phase boundary, it has good dielectric, ferroelectric and piezoelectric properties, and has been widely used as dielectric materials for energy storage capacitors.

[0003] Existing methods for preparing PZT thin films include laser pulse precipitation, magnetron sputtering, metal organic chemical vapor deposition, chemical solution deposition, sol-gel method, etc.; among them, magnetron sputtering has many advantages such as uniform film surface, controllable deposition rate, short cycle, few impurities, and suitability for large-area deposition, and is widely used.

[0004] At present, in order to obtain PZT films with excellent dielectric properties, doping, crystallization temperature regulation and heterojunction addition are usually adopted. Although the above methods can improve the dielectric properties of lead zirconate titanate films to a certain extent, there are problems such as the dielectric constant of the material dropping rapidly near the resonant frequency, or the high dielectric constant value is in the low frequency range, and the dielectric constant in the high frequency range is not high, which is not conducive to the actual production and application of lead zirconate titanate films. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for preparing a high dielectric constant lead zirconate titanate film.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high dielectric constant lead zirconate titanate film, characterized in that it comprises the following steps:

[0007] 1) PbO, TiO2 and ZrO2 are mixed in a certain mass ratio, polyvinyl alcohol (PVA) aqueous solution is added after mixing, fully ground, pressed into a target, and then sintered once;

[0008] 2) After ball milling the sintered material in step 1), a transition metal oxide is added thereto, the material is fully ground, pressed into a target, and then subjected to secondary sintering to obtain a doped lead zirconate titanate target;

[0009] 3) Depositing a lead zirconate titanate thin film on the sintered doped lead zirconate titanate target by magnetron sputtering, and performing sputtering at a certain power density;

[0010] 4) The lead zirconate titanate film is subjected to rapid heat treatment to obtain a high dielectric constant lead zirconate titanate film.

[0011] Preferably, in step 1), the purity of PbO, TiO2 and ZrO2 is higher than 99.99%, and the purity of PbO, TiO2 and ZrO2 is higher than 99.99%. x Ti 1-x )O3 (0≤x≤1) is weighed, where x is between 0.48 and 0.95.

[0012] Preferably, in step 1), the concentration of polyvinyl alcohol (PVA) is 5 wt %, and the polyvinyl alcohol (PVA) is added at a dosage of 1 drop per 1 g of total mass.

[0013] Preferably, in step 1) and step 2), the grinding time is 0.1 hour to 3 hours, the pressure of pressing into the target is 3 MPa to 10 MPa, and the residence time is 10 seconds to 30 seconds.

[0014] Preferably, in step 1) and step 2), after being pressed into a target, it needs to be sintered in a high-temperature muffle furnace. The sintering is divided into two processes: pre-sintering and calcining. The burying method is used throughout the process. The pre-sintering temperature is 600°C to 700°C, and the insulation time is 0.5 hour to 2 hours.

[0015] Preferably, in step 1), the calcination temperature is 900° C. to 1100° C. and the holding time is 3 hours to 8 hours.

[0016] Preferably, in step 2), the calcination temperature is 1000° C. to 1200° C., and the holding time is 3 hours to 8 hours.

[0017] Preferably, in step 2), the transition metal oxide is one or a mixture of oxides of Y, V, Hf, Mo, Cr, Mn, Co, Cu, and Zn, wherein the mass of the added transition metal oxide is 0.01% to 0.1% of the total mass.

[0018] Preferably, in step 3), the argon flow rate during the sputtering process is 50 sccm, the ignition pressure is 0.9 Pa, and the power density is 4 W / cm 2 ~6W / cm 2 .

[0019] Preferably, in step 4), the temperature of the rapid thermal treatment is 400° C. to 500° C., and the holding time is 5 minutes to 20 minutes.

[0020] From the above description of the structure of the present invention, it can be seen that compared with the prior art, the present invention has the following advantages:

[0021] 1. The present invention has simple operation method, stable performance, good repeatability, low cost and is suitable for large-scale production.

[0022] 2. The preparation method of the present invention improves the shortcomings of the single-component PZT film with uneven structure and poor electrical properties, and effectively improves the dielectric properties of the lead zirconate titanate film by doping. The relative dielectric constant of the lead zirconate titanate film prepared by the present invention can reach 1210, and the dielectric loss is only 0.00872. A high dielectric constant is maintained in a wide frequency range. The resonant frequency is moved toward the high frequency direction, which is suitable for the preparation of high-frequency devices.

[0023] 3. The present invention reduces the annealing temperature of the film, which not only reduces the problem of product yield caused by the volatilization of its elements, but also improves the overall energy storage density of the film, and is compatible with the monolithic integration process of ferroelectric microdevices. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0025] Figure 1 The dielectric spectrum curve of the lead zirconate titanate film prepared in Example 1;

[0026] Figure 2 The dielectric spectrum curve of the lead zirconate titanate film prepared in Example 2;

[0027] Figure 3 The dielectric spectrum curve of the lead zirconate titanate film prepared in Comparative Example 1;

[0028] Figure 4 This is the dielectric spectrum curve of the lead zirconate titanate film prepared in Control Example 2. DETAILED DESCRIPTION

[0029] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0030] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0031] Example 1

[0032] This embodiment provides a method for preparing a high dielectric constant lead zirconate titanate film, and the specific steps are:

[0033] Step 1: PbO (purity higher than 99.99%), TiO2 (purity higher than 99.99%) and ZrO2 (purity higher than 99.99%) are mixed according to the Pb(Zr x Ti 1-x)O3 (0≤x≤1) was weighed, where x was 0.48. A polyvinyl alcohol (PVA) aqueous solution with a concentration of 5 wt% was added and fully ground for 1.5 hours; the tablet press was pressed at a pressure of 6 MPa and a residence time of 20 seconds. The first sintering was carried out in a high-temperature muffle furnace using the buried firing method, with a pre-sintering temperature of 630°C and a heat preservation of 1.5 hours. The calcination temperature was 1000°C and the heat preservation was 5 hours.

[0034] Step 2: After ball milling the material after the first sintering, add 0.05% Y2O3 of the total mass. Grind thoroughly for 2 hours; the pressure of the tablet press is 8Mpa, the residence time is 15 seconds, and the pressing is formed. The second sintering is carried out in a high-temperature muffle furnace using the buried firing method, the pre-firing temperature is 670°C, and the heat is kept for 2 hours. The calcination temperature is 1050°C and the heat is kept for 5 hours. After sintering, a doped lead zirconate titanate target is made.

[0035] Step 3: Deposition of lead zirconate titanate thin film by magnetron sputtering with a power density of 4.5 W / cm 2 Sputtering was performed with an argon gas flow rate of 50 sccm and a starting pressure of 0.9 Pa to form a film with a thickness of 150 nm.

[0036] Step 4: Using a rapid annealing process, the doped PZT film prepared in step 3 is placed in a rapid annealing furnace for annealing at a temperature of 450° C. for 10 minutes.

[0037] Example 2

[0038] This embodiment provides a method for preparing a high dielectric constant lead zirconate titanate film, and the specific steps are:

[0039] Step 1: PbO (purity higher than 99.99%), TiO2 (purity higher than 99.99%) and ZrO2 (purity higher than 99.99%) are mixed according to the Pb(Zr x Ti 1-x )O3 (0≤x≤1) was weighed, where x was 0.55. A polyvinyl alcohol (PVA) aqueous solution with a concentration of 5 wt% was added and fully ground for 2 hours; the tablet press pressure was 7Mpa, the residence time was 25 seconds, and the tablet was pressed into shape. The first sintering was carried out in a high-temperature muffle furnace using the buried firing method, the pre-firing temperature was 670℃, and the temperature was kept for 1 hour. The calcination temperature was 980℃ and the temperature was kept for 4 hours.

[0040] Step 2: After ball milling the material after the first sintering, add 0.01% VO2 and 0.02% MnO. Grind thoroughly for 2.5 hours; the pressure of the tablet press is 7Mpa, the residence time is 10 seconds, and the pressing is formed. The second sintering is carried out in a high-temperature muffle furnace using the buried firing method, the pre-firing temperature is 650°C, and the heat preservation is 0.8 hours. The calcination temperature is 1100°C and the heat preservation is 6 hours. After sintering, a doped lead zirconate titanate target is made.

[0041] Step 3: Deposition of lead zirconate titanate thin film by magnetron sputtering, with a power density of 5.0 W / cm 2 Sputtering was performed with an argon gas flow rate of 50 sccm and a starting pressure of 0.9 Pa to form a film with a thickness of 120 nm.

[0042] Step 4: Using a rapid annealing process, the doped PZT film prepared in step 3 is placed in a rapid annealing furnace for annealing at a temperature of 500° C. for 15 minutes.

[0043] Comparative Example 1

[0044] This embodiment provides a method for preparing a high dielectric constant lead zirconate titanate film, and the specific steps are:

[0045] Step 1: PbO (purity higher than 99.99%), TiO2 (purity higher than 99.99%) and ZrO2 (purity higher than 99.99%) are mixed according to the Pb(Zr x Ti 1-x )O3 (0≤x≤1) was weighed, where x was 0.48. A polyvinyl alcohol (PVA) aqueous solution with a concentration of 5 wt% was added and fully ground for 1.5 hours; the tablet press was pressed at a pressure of 6 MPa and a residence time of 20 seconds. The first sintering was carried out in a high-temperature muffle furnace using the buried firing method, with a pre-sintering temperature of 630°C and a heat preservation of 1.5 hours. The calcination temperature was 1000°C and the heat preservation was 5 hours.

[0046] Step 2: After the material after the first sintering is ball-milled and fully ground for 2 hours; the pressure of the tablet press is 8Mpa, the residence time is 15 seconds, and the pressing is formed. The second sintering is carried out in a high-temperature muffle furnace using the buried firing method, the pre-firing temperature is 670°C, and the heat is kept for 2 hours. The calcination temperature is 1050°C and the heat is kept for 5 hours. After sintering, the doped lead zirconate titanate target is made.

[0047] Step 3: Deposition of lead zirconate titanate thin film by magnetron sputtering with a power density of 4.5 W / cm 2 Sputtering was performed with an argon gas flow rate of 50 sccm and a starting pressure of 0.9 Pa to form a film with a thickness of 120 nm.

[0048] Step 4: Using a rapid annealing process, the doped PZT film prepared in step 3 is placed in a rapid annealing furnace for annealing at a temperature of 450° C. for 10 minutes.

[0049] Comparative Example 2

[0050] This embodiment provides a method for preparing a high dielectric constant lead zirconate titanate film, and the specific steps are:

[0051] Step 1: PbO (purity higher than 99.99%), TiO2 (purity higher than 99.99%) and ZrO2 (purity higher than 99.99%) are mixed according to the Pb(Zr x Ti 1-x )O3 (0≤x≤1) was weighed, where x was 0.55. A polyvinyl alcohol (PVA) aqueous solution with a concentration of 5 wt% was added and fully ground for 2 hours; the tablet press pressure was 7Mpa, the residence time was 25 seconds, and the tablet was pressed into shape. The first sintering was carried out in a high-temperature muffle furnace using the buried firing method, the pre-firing temperature was 670℃, and the temperature was kept for 1 hour. The calcination temperature was 980℃ and the temperature was kept for 4 hours.

[0052] Step 2: After ball milling the material after the first sintering, add 0.01% VO2 and 0.02% MnO. Grind thoroughly for 2.5 hours; the pressure of the tablet press is 7Mpa, the residence time is 10 seconds, and the pressing is formed. The second sintering is carried out in a high-temperature muffle furnace using the buried firing method, the pre-firing temperature is 650°C, and the heat preservation is 0.8 hours. The calcination temperature is 1100°C and the heat preservation is 6 hours. After sintering, a doped lead zirconate titanate target is made.

[0053] Step 3: Deposition of lead zirconate titanate thin film by magnetron sputtering, with a power density of 5.0 W / cm 2 Sputtering was performed with an argon gas flow rate of 50 sccm and a starting pressure of 0.9 Pa to form a film with a thickness of 120 nm.

[0054] The dielectric spectrum curves of the above lead zirconate titanate films are shown in Figures 1 to 4. The relative dielectric constant of Example 1 can reach 1148, and the dielectric loss is 0.00939; the relative dielectric constant of Example 2 can reach 1210, and the dielectric loss is 0.00872; it can be seen that the method of the present invention can be used to prepare a lead zirconate titanate film with a high dielectric constant and low dielectric loss. Except that the transition metal oxide is not doped in Control Example 1, the rest of the process is exactly the same as the preparation process of Example 1. The relative dielectric constant of Control Example 1 can reach 1013, and the dielectric loss is 0.01146. Example 1 maintains a high dielectric constant in a wider frequency range, while Control Example 1 only has a higher dielectric constant value at the resonant frequency. In the rest of the frequency range, the dielectric constant drops rapidly. In addition, compared with Control Example 1, the resonant frequency of Example 1 moves toward the high frequency direction. Except that there is no rapid annealing of the film at the end, the rest of the process of Control Example 2 is exactly the same as the preparation process of Example 2. The relative dielectric constant of Control Example 2 can reach 80.7, and the dielectric loss is 0.04187, indicating that the dielectric constant of Example 2 is significantly improved compared with Control Example 2.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high dielectric constant lead zirconate titanate film, characterized in that: The steps include: 1) PbO, TiO2 and ZrO2 are mixed in a certain mass ratio, polyvinyl alcohol (PVA) aqueous solution is added after mixing, fully ground, pressed into a target, and then sintered once; 2) After ball milling the sintered material in step 1), a transition metal oxide is added thereto, fully ground, pressed into a target, and then subjected to secondary sintering to prepare a doped lead zirconate titanate target; wherein the transition metal oxide is one or a mixture of several oxides of Y, V, Hf, Mo, Cr, Mn, Co, Cu, and Zn, and the mass of the added transition metal oxide is 0.01% to 0.1% of the total mass; 3) The lead zirconate titanate thin film was deposited on the sintered doped lead zirconate titanate target by magnetron sputtering, and the sputtering was performed at a certain power density; the argon flow rate during the sputtering process was 50 sccm, the starting pressure was 0.9 Pa, and the power density was 4 W / cm 2 ~6W / cm 2 ; 4) subjecting the lead zirconate titanate film to rapid thermal treatment to obtain a high dielectric constant lead zirconate titanate film; wherein the rapid thermal treatment temperature is 400° C. to 500° C., and the holding time is 5 minutes to 20 minutes.

2. The method for preparing a high dielectric constant lead zirconate titanate film according to claim 1, characterized in that: In step 1), the purity of PbO, TiO2 and ZrO2 is higher than 99.99%, and the purity of PbO, TiO2 and ZrO2 is higher than 99.99%. x Ti 1-x )O3 (0≤x≤1) is weighed, where x is between 0.48 and 0.

95.

3. The method for preparing a high dielectric constant lead zirconate titanate film according to claim 1, characterized in that: In step 1), the concentration of polyvinyl alcohol (PVA) is 5 wt %, and the polyvinyl alcohol (PVA) is added at a dosage of 1 drop per 1 g of the total mass.

4. The method for preparing a high dielectric constant lead zirconate titanate film according to claim 1, characterized in that: In step 1) and step 2), the grinding time is 0.1 hour to 3 hours, the pressure of pressing into the target is 3Mpa to 10Mpa, and the residence time is 10 seconds to 30 seconds.

5. The method for preparing a high dielectric constant lead zirconate titanate film according to claim 1, characterized in that: In step 1) and step 2), after being pressed into a target, it needs to be sintered in a high-temperature muffle furnace. The sintering is divided into two processes: pre-firing and calcining. The burial method is used throughout the process. The pre-firing temperature is 600°C to 700°C, and the insulation time is 0.5 hours to 2 hours.

6. The method for preparing a high dielectric constant lead zirconate titanate film according to claim 5, characterized in that: In step 1), the calcination temperature is 900° C. to 1100° C., and the holding time is 3 hours to 8 hours.

7. The method for preparing a high dielectric constant lead zirconate titanate film according to claim 5, characterized in that: In step 2), the calcination temperature is 1000° C. to 1200° C., and the holding time is 3 hours to 8 hours.

Citation Information

Patent Citations

  • ZnO doped lead titanate piezoelectric ceramics and preparation method thereof

    CN101665355A